A resolução de problemas matemáticos sob diferentes perspectivas: um olhar para a resolução de problemas geométricos - Silva, Stenio Rocha (2022)
The objective of this work is to look for strategies, methodologies, techniques, among other elements, aiming at teaching and learning through the resolution of geometric problems. The literature review was guided by the work of mathematicians directly involved with problem sol ving and who participated and contributed in Mathematical Circles or Mathematics Olympiads, rescuing their experiences and experiments. The research presented a problem solving filled with logical techniques and punctuated by mathematical rigor, on the one hand, but revealed a strong contribution of psychological strategies, mental attitudes, intuitive and inventive. A set of activities are proposed as an initial tool for teachers to discover and encourage their students to find their mental potential for problem solving.